SRC kinase-mediated signaling pathways and targeted therapies in breast cancer - Juan Luo; Hailin Zou; Yibo Guo; Tongyu Tong; Liping Ye; Chengming Zhu; Liang Deng; Bo Wang; Yihang Pan; Peng Li (Breast Cancer Research, 2022)
Abstract Breast cancer (BC) has been ranked the most common malignant tumor throughout the world and is also a leading cause of cancer-related deaths among women. SRC family kinases (SFKs) belong to the non-receptor tyrosine kinase (nRTK) family, which has eleven members sharing similar structure and function. Among them, SRC is the first identified proto-oncogene in mammalian cells. Oncogenic overexpression or activation of SRC has been revealed to play essential roles in multiple events of BC progression, including tumor initiation, growth, metastasis, drug resistance and stemness regulations. In this review, we will first give an overview of SRC kinase and SRC-relevant functions in various subtypes of BC and then systematically summarize SRC-mediated signaling transductions, with particular emphasis on SRC-mediated substrate phosphorylation in BC. Furthermore, we will discuss the progress of SRC-based targeted therapies in BC and the potential future direction.